1990
DOI: 10.1093/bja/64.4.474
|View full text |Cite
|
Sign up to set email alerts
|

Halothane Metabolism in Children

Abstract: Halothane (1% v/v inspired) was administered for 60 min to six children of mean age 74 months (range 14-119 months). Uptake of halothane was measured from the difference in the concentration in inspired and expired gas and varied from 176 to 310 mg kg-1, depending on minute ventilation. After administration of halothane ceased, its elimination in expired gas was measured in four patients until the conclusion of anaesthesia; 32-37% of the absorbed halothane was expired 90 min after halothane administration ceas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Such induction might be caused by other drugs including barbiturates, phenytoin and rifampin. It has been suggested that the very low incidence of halothane hepatitis in children may be explained in part by immaturity of the reductive metabolic pathways, although recently this has been challenged (Wark et al 1990). Although some have recommended that repeated exposure to halothane be avoided in children, the fact that millions of repeated halothane anaesthetics have been administered to children without ill-effects lend support to our position that there is insufficient evidence at present to avoid repeat halothane anaesthetics in infants and children.…”
Section: Hepaticmentioning
confidence: 99%
“…Such induction might be caused by other drugs including barbiturates, phenytoin and rifampin. It has been suggested that the very low incidence of halothane hepatitis in children may be explained in part by immaturity of the reductive metabolic pathways, although recently this has been challenged (Wark et al 1990). Although some have recommended that repeated exposure to halothane be avoided in children, the fact that millions of repeated halothane anaesthetics have been administered to children without ill-effects lend support to our position that there is insufficient evidence at present to avoid repeat halothane anaesthetics in infants and children.…”
Section: Hepaticmentioning
confidence: 99%
“…Cohen and co-workers applied radiolabeled halothane to eight patients and incorporation of radiolabel into a fraction identified as BCDFE-NAC suggested that this should be a major metabolite of halothane [34]. However, Wark and co-workers have failed to detect this metabolite in urine of six halothaneanesthetized children [63], and no acetyl BCDFE has been observed in any of 43 urines tested [64] ted that their inability to find substantial amounts of BCDFE-NAC and the unusual time course of excretion described by Cohen and co-workers [34] led them to doubt whether the substance measured by this group was a genuine metabolite of halothane [64]. Wark and coworkers obtained the urines from six children who had been subjected to halothane anesthesia applied via a non-rebreathing circuit, i. e. an open system.…”
Section: Halothane and Isofluranementioning
confidence: 99%
“…For this reason, data from adult case reports should not be extrapolated to the paediatric population (41). Hepatitis is believed to be more common with halothane due to increased metabolism of around 20% (42–45) vs 2–5% of sevoflurane (44,46), 0.2–0.6% of isoflurane (44) and 0.02% (minimal) of desflurane (47–49). Sevoflurane is not metabolized to trifluoroacetylated proteins and therefore repeated exposures are unlikely to promote immune‐mediated toxicity (46).…”
Section: Halothane Hepatitismentioning
confidence: 99%
“…Sevoflurane is not metabolized to trifluoroacetylated proteins and therefore repeated exposures are unlikely to promote immune‐mediated toxicity (46). The extent of halothane metabolism is similar in adults and children and therefore does not explain the reduced incidence of hepatitis in children (45). A review from Great Ormond Street Hospital for Children found an incidence of halothane hepatitis of 1 : 82 000 halothane anaesthetics in children (50).…”
Section: Halothane Hepatitismentioning
confidence: 99%